Interleukin-1 Signaling Prevents Alveolar Macrophage Depletion during Influenza and Streptococcus pneumoniae Coinfection - Bansal, Shruti (J Immunol, 2018)
Influenza and bacterial coinfection is a significant cause of hospitalization and death in humans during influenza epidemics and pandemics. However, the fundamental protective and pathogenic mechanisms involved in this complex virus-host-bacterium interaction remain incompletely understood. In this study, we have developed mild to lethal influenza and pneumococcal coinfection models for comparative analyses of disease pathogenesis. Specifically, WT and interleukin-1 receptor type 1-deficient (Il1r1(−/−)) mice were infected with influenza virus, and then super-challenged with noninvasive pneumococcal serotype 14 (Spn14) or 19A (Spn19A). The coinfections were followed by comparative analyses of inflammatory responses and animal protection. We found that resident alveolar macrophages are efficient in clearance of both pneumococcal serotypes in the absence of influenza infection; on the other hand, they are essential for airway control of Spn14 infection but not Spn19A. In agreement, TNF-α and neutrophils play a compensatory protective role in secondary bacterial infection associated with Spn19A; however, the essential requirement for AM-mediated clearance significantly enhances the virulence of Spn14 during post-influenza pneumococcal infection. Furthermore, we show that although IL-1 signaling is not required for host defense against pneumococcal infection alone, it is essential for sustaining antibacterial immunity during post-influenza pneumococcal infection, as evidenced by significantly aggravated bacterial burden and animal mortality in Il1r1(−/−) mice. Mechanistically, we show that through preventing AM depletion, inflammatory cytokine IL-1 signaling is critically involved in host resistance to influenza and pneumococcal coinfection.